Pengaruh Good Corporate Governance, Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Peraih The Indonesia Most Trusted Company–CGPI Yang Go Publik Di Bursa Efek Indonesia (Bei) Periode 2013-2016 - Agus Supriyatno; Syifa Fauziyyah (STES Islamic Village, 2020)
The aim of this study is to investigate the impact of Good Coorporate Governance, Profitability, Leverage toward the coorporate value. The sampling in this study used purposive sampling from extractive companies and manufacturing ranked The Most Trusted Companies Companies - Corporate Governance Perception Index (IMTC - CGPI) listed on the Stock Exchange from 2013-2016 and obtained 32 samples. This study is tested using multiple regression analysis technique with SPSS 22. The findings show that (1) CGPI has a significance value of 0.723> 0.05 so that CG Index does not negatively affect the company value. (2) Leverage has a significance value of 0.821> 0.05, so leverage does not negatively affect the value of the company. (3) Profitability has a significance value of 0.000 <0.05 so that profitability has a positive effect on firm value. (4) Simultaneously CG Index, Leverage, Profitability have a significant effect to company value.